Social Security Measures in Mining Industries: A Study with Reference to Manganese and Iron Ore Industries in Ballari District, Karnataka - S., Sadyojathappa (Prabandhan: Indian Journal of Management, 2015)
Social security is one of the key components of labour welfare. Labour welfare refers to services, amenities, and facilities provided to the employees that improve their working conditions as well as their standards of living. Social security is a benefit provided by entrepreneurs to protect not only the employees, but also their family members through financial security, including health care. Social security envisages that the employees shall be protected against all types of social risks that may cause undue hardships to them. Employees play an important role in the industrial development of a country. The human resource managers are really concerned with the management of people at work. Hence, it is necessary to secure the cooperation of labour or the employee force in order to increase production and to earn more profits. In the new economy, the freedom of the workers as human beings has been exposed to new dimensions of invasions and controls. To dispense with unsatisfactory economic situations in the labour field, controls through State regulations have become necessary. The main objective of the present study was to inquire into the social security measures provided to employees in the working mining units of Ballari District, Karnataka.